Teaching creative writing the essential guide - Vanderslice, Stephanie (Bloomsbury Academic, 2024)
"The only textbook of its kind, this all-in-one introduction guides you through the history, theories and practices of creative writing you need to know to teach this ever-expanding and infinitely rewarding subject successfully in higher education. Asking you to think reflectively about the discipline throughout, this book offers a bridge between teaching and learning of the subject to help you develop effective and informed methods that will enliven your classroom and help you discover the best practice for you. Based on the author's two decades of teaching and research in creative writing theory and pedagogy, and on feedback from a range of instructors in the field, Stephanie Vanderslice brings forward this essential companion for students and teachers engaging with the study and instruction of creative writing. Written in Vanderslice's trademark cogent, conversational style, Teaching Creative Writing gives you the tools to understand creative writing as a subject and a practice and offers you a ready-to-use blueprint for planning your first creative writing classes. It covers such critical topics as: - How research into the development of the creative writer might influence your classroom environment - The need to free students from damaging myths and pervasive lore - The use of revision and editing - Creating inclusive classroom spaces and workshops - The place of genre in creative writing - Teaching students to work multi-modally - How to assess and grade work - Introducing students to the literary community - Teaching creative writing online Building on what it means to teach creative writing in the 21st century, this book leads you through creating your own syllabi, course plans, and statements of teaching philosophies, features capsule interviews with experts on key topics, and includes an online companion resource which features teacher guides to using the book"--